2020
DOI: 10.1542/peds.2019-3204
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Necrotizing Pneumonia: Another Potential Life-threatening Complication of Vaping?

Abstract: An adolescent girl with a history of frequent electronic cigarette use of nicotine was hospitalized with severe necrotizing pneumonia. Blood cultures obtained before the administration of empirical broad-spectrum intravenous antibiotics had positive results for the growth of Fusobacterium necrophorum. The pathogen is an uncommon but well-known cause of anaerobic pneumonia with unique features that are collectively referred to as Lemierre syndrome or postanginal sepsis. The syndrome begins as a pharyngeal infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Metronidazole is recommended in combination with b-lactam antibiotics (Sacco et al, 2019;Tay and Vasoo, 2022). In current research, the average duration of antibiotic use was as long as 2-4 weeks, and some severe patients were treated for 8-16 weeks (Sheehan et al, 2019;Gama et al, 2020;Tamura et al, 2020;El Chebib et al, 2020;Repper et al, 2020;Monroe and Amlie-Lefond, 2018;Dal Bo et al, 2019;Whittle et al, 2018;Rana et al, 2017;Sinatra and Alander, 2017;He et al, 2015;Creemers-Schild et al, 2014). In this case, to cover the anaerobic bacteria as well as some pathogenic or coinfected G-bacilli and streptococci, the broad-spectrum carbapenem antibiotics were initially used empirically.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Metronidazole is recommended in combination with b-lactam antibiotics (Sacco et al, 2019;Tay and Vasoo, 2022). In current research, the average duration of antibiotic use was as long as 2-4 weeks, and some severe patients were treated for 8-16 weeks (Sheehan et al, 2019;Gama et al, 2020;Tamura et al, 2020;El Chebib et al, 2020;Repper et al, 2020;Monroe and Amlie-Lefond, 2018;Dal Bo et al, 2019;Whittle et al, 2018;Rana et al, 2017;Sinatra and Alander, 2017;He et al, 2015;Creemers-Schild et al, 2014). In this case, to cover the anaerobic bacteria as well as some pathogenic or coinfected G-bacilli and streptococci, the broad-spectrum carbapenem antibiotics were initially used empirically.…”
Section: Discussionmentioning
confidence: 97%
“…For pediatric patients, as the immune function was not complete, F. necrophorum was more direct and rapid-invading (Brennan and Garrett, 2019). Due to the high virulence and invasiveness of the bacteria, the body would directly respond to severe sepsis, leading to hemodynamic failure and multiple-organ failure prior to internal jugular vein thrombosis and septic embolism (Sheehan et al, 2019;Tamura et al, 2020;El Chebib et al, 2020;Habib et al, 2019). In this case, in the absence of suppurative thrombophlebitis of the internal jugular vein, the F. necrophorum infection progressed very rapidly, leading to septic shock within 24 h and causing life-threatening failure of vital organs, including respiratory failure and heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of inappropriate antibiotics can also prolong hospital stay [12]. If patients are not promptly diagnosed and treated, they can develop severe pneumonia and multiple organ failure, which can be fatal [13]. Treatment should include a prolonged course of intravenous beta-lactam antibiotics in combination with metronidazole [14].…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal alteration can be secondary to accidental or surgical local trauma, primary viral or bacterial infections, and chronic nicotine irritation [ 8 , 23 ]. Notably, our patients had an early habit of smoking and vaping, which could be acknowledged as an emerging risk factor for LS in adolescents [ 9 ]. Some authors have reported an association with Epstein-Barr virus pharyngitis, but the mechanism remains uncertain [ 5 , 6 , 29 , 37 39 ].…”
Section: Introductionmentioning
confidence: 99%